Influence of relative density on quasi-static and fatigue failure of lattice structures in Ti6Al4V produced by laser powder bed fusion - Markel Alaña (Nature Portfolio, 2021)
Abstract Lattice structures produced by additive manufacturing have been increasingly studied in recent years due to their potential to tailor prescribed mechanical properties. Their mechanical performances are influenced by several factors such as unit cell topology, parent material and relative density. In this study, static and dynamic behaviors of Ti6Al4V lattice structures were analyzed focusing on the criteria used to define the failure of lattices. A modified face-centered cubic (FCCm) lattice structure was designed to avoid the manufacturing problems that arise in the production of horizontal struts by laser powder bed fusion. The Gibson–Ashby curves of the FCCm lattice were obtained and it was found that relative density not only affects stiffness and strength of the structures, but also has important implications on the assumption of macroscopic yield criterion. Regarding fatigue properties, a stiffness based criterion was analyzed to improve the assessment of lattice structure failure in load bearing applications, and the influence of relative density on the stiffness evolution was studied. Apart from common normalization of S–N curves, a more accurate fatigue failure surface was developed, which is also compatible with stiffness based failure criteria. Finally, the effect of hot isostatic pressing in FCCm structures was also studied.